If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(4p + -4) = 0 Reorder the terms: 8(-4 + 4p) = 0 (-4 * 8 + 4p * 8) = 0 (-32 + 32p) = 0 Solving -32 + 32p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 32p = 0 + 32 Combine like terms: -32 + 32 = 0 0 + 32p = 0 + 32 32p = 0 + 32 Combine like terms: 0 + 32 = 32 32p = 32 Divide each side by '32'. p = 1 Simplifying p = 1
| (x+1)(3x-2)-2x-4=0 | | X^2+8x-90=0 | | (2)(-4)= | | 9x(9x-16)+64=0 | | 8x+2=3(3x+8) | | 25x+25=-345-15x | | 16/z=-8/1 | | x+y=100.45 | | 2x-16=7x+9 | | 14x-10=12x+6 | | 12x-16=3x-9 | | (13/3)-4-3 | | -(-8x)=(-35) | | 13/3-4-3 | | .25x^2+x+1=0 | | 4(x-5)=6-2x+13+7+2x+2 | | 14x-38=8x+4 | | 26x+21=-23x-9 | | 13x=42+5x | | 100cosx=60 | | r(3-2)=4 | | 2x+8=16+4x | | 27x^3-9x^2+15x= | | 3.7y+9=8.1y-17.4 | | 2x^2+14x+49=9x^2-42x+49 | | 2/9(x-5/4)=-1/9 | | 2x(34)-42=w | | (2x+15)+11x=180 | | 9=-7x | | 3x^2+1ox-77=0 | | (-1-2i)(6-2i)= | | (-5-4i)+(-4+7i)= |